Europiella livida Reuter 1906 - Duwal, Ram Keshari; Jung, Sunghoon; Yasunaga, Tomohide; Lee, Seunghwan (Zenodo, 2016)
32. Europiella livida (Reuter, 1906) Plagiognathus lividus : Reuter, 1906: 73 (sp. nov.); Kerzhner (1988b): 855 (key) Europiella livida : Schuh et al. (1995): 390 (comb. nov.); Schuh (1995): 316 (cat.); Kerzhner & Josifov (1999): 346 (cat.); Vinokurov et al. (2010): 135 (cat.); Duwal et al. (2014a): 389 (diag.). Distribution . Asia: South Korea (GG) (Duwal et al. 2014a), China (Northeast, North, Southeast), Russia (Far East) (Kerzhner & Josifov 1999). Host . Artemisia gigantea Kitamura (Asteraceae) (Kerzhner 1988b). 33. Europiella miyamotoi (Kerzhner, 1988) (Figure plate 3) Plagiognathus miyamotoi Kerzhner, 1988a: 64 (sp. nov.) Europiella miyamotoi : Schuh et al. (1995): 391 (comb. nov.); Schuh (1995): 316 (cat.); Kerzhner & Josifov (1999): 346 (cat.); Yasunaga (2001a): 164 (diag., fig.); Vinokurov et al. (2010): 135 (cat.); Duwal et al. (2014a): 390 (diag., figs.). Distribution . Asia: South Korea (GB) (Duwal et al. 2014a), Japan (Yasunaga 2001a), Russia (Sakhalin & Kuril Is.) (Kerzhner 1988a). Host . Artemisia gigantea Kitamura (Asteraceae) (Kerzhner 1988a). Published as part of Duwal, Ram Keshari, Jung, Sunghoon, Yasunaga, Tomohide & Lee, Seunghwan, 2016, Annotated catalogue of the Phylinae (Heteroptera: Miridae) from the Korean Peninsula, pp. 101-134 in Zootaxa 4067 (2) on page 111, DOI:10.11646/zootaxa.4067.2.1, http://zenodo.org/record/270595